SNHG9, a Papillary Thyroid Cancer Cell Exosome-Enriched lncRNA, Inhibits Cell Autophagy and Promotes Cell Apoptosis of Normal Thyroid Epithelial Cell Nthy-ori-3 Through YBOX3/P21 Pathway - Wen, Duo; Liu, Wan-lin; Lu, Zhong-wu; Cao, Yi-ming; Ji, Qing-hai; Wei, Wen-jun (Frontiers in Oncology, 2021)
Thyroid cancer is the most common type of endocrine malignancy. Although the general prognosis is good, the treatment of advanced disease is still challenging. Exosomes are vesicle units containing specific components that transmit information between cells. In order to explore its role in papillary thyroid cancer (PTC), our study screened exosome enriched lncRNA SNHG9 by lncRNA chip and explored its biological function. We used lncRNA chips combined with bioinformatics analysis to screen lncRNA SNHG9 enriched in exosomes. GO analysis suggested its relationship with autophagy and apoptosis. Quantitative PCR showed SNHG9 was highly expressed in PTC cells and exosomes and its correlation with PTC tumor size was analyzed by clinical characteristics. SNHG9 could inhibit the protective cell autophagy induced by starvation of human normal thyroid epithelial cell line Nthy-ori-3 and promote its apoptosis through PTC cell exosomes. RNA-pull down combined with protein spectrum showed that SNHG9 could interact with YBOX3. Western blot and RNA immunoprecipitation further confirmed their interaction. Western blot showed that SNHG9 could induce degradation of YBOX3, thus interfering with the stability of P21 mRNA and inducing cell apoptosis. In conclusion, our study identified SNHG9 as a PTC cell exosome-enriched lncRNA. SNHG9 could inhibit cell autophagy and promote apoptosis of Nthy-ori-3 cell through YBOX3/P21 pathway.